Notch3 promotes 3T3‐L1 pre‐adipocytes differentiation by up‐regulating the expression of LARS to activate the mTOR pathway. Issue 1 (21st November 2019) - Guo, Yuxian; Tan, Junyu; Xiong, Wei; Chen, Shuzhao; Fan, Liping; Li, Yaochen
Abstract: Adipocytes constitute a major component of the tumour microenvironment. Numerous studies have shown that adipocytes promote aggressiveness and invasion by stimulating cancer cells proliferation and modulating their metabolism. Herein, we reported that Notch3 promotes mouse 3T3‐L1 pre‐adipocytes differentiation by performing the integrative transcriptome and TMT‐based proteomic analyses. The results revealed that aminoacyl‐tRNA_biosynthesis pathway was significantly influenced with Nocth3 change during 3T3‐L1 pre‐adipocytes differentiation, and the expression of LARS in this pathway was positively correlated with Notch3. Published studies have shown that LARS is a sensor of leucine that regulates the mTOR pathway activity, and the latter involves in adipogenesis. We therefore supposed that Notch3 might promote 3T3‐L1 pre‐adipocytes differentiation by up‐regulating LARS expression and activating mTOR pathway. CHIP and luciferase activity assay uncovered that Notch3 could transcriptionally regulate the expression of LARS gene. Oil Red staining identified a positive correlation between Notch3 expression and adipocytic differentiation. The activation of mTOR pathway caused by Notch3 overexpression could be attenuated by knocking down LARS expression. Altogether, our study revealed that Notch3 promotes adipocytic differentiation of 3T3‐L1 pre‐adipocytes cells by up‐regulating LARS expression and activating the mTOR pathway, which might be an emerging target for obesity treatment.